Hypervalent Iodine (III) Catalyzed Regio- and Diastereoselective Aminochlorination of Tailored Electron Deficient Olefins via GAP Chemistry - Rahman, Anis Ur; Zarshad, Nighat; Zhou, Peng; Yang, Weitao; Li, Guigen; Ali, Asad (Frontiers in Chemistry, 2020)
Herein, we report a protocol for highly efficient hypervalent iodine (III) mediated, Group Assisted Purification (GAP) method for the regio- and stereoselective aminochlorination of electron-deficient olefins. A series of vicinal chloramines with multi functionalities were acquired in moderate to excellent yields (45-94%), by merely mixing the GAP auxiliary-anchored substrates with dichloramine T and tosylamide as chlorine/nitrogen sources and iodobenzene diacetate as a catalyst. The vicinal chloramines were obtained without any column chromatographic purification and recrystallization simply by washing the reaction mixture with minimum amount of common inexpensive solvents and thus avoiding wastage of silica, solvents, time and labour.The GAP auxillary can be recovered and reused. This strategy is easy to handle, cost-effective, greener, sustainable, environmentally benign and broadly applicable for the syntheses of vicinal haloamines from various electron-deficient alkenes.